Lebanon: An Ordinary “Consociational Democracy” in the Regional Context - A. V. Sarabiev (Vestnik MGIMO-Universiteta)
Lebanon has a number of features that determine its special position in the region and its importance in the system of relations between the Middle East states. An important role in this is played by the ideological and strategic aspects of world politics in the region in which Lebanon is organically inscribed in both the historical and geopolitical plans. The stability of a country that has passed through a long civil war makes it stand out from a number of states in the region. The author's hypothesis is that the reason for the extraordinary stability — of Lebanese society, the system of state power, political elites, economic ties and foreign policy contacts, despite all the negative regional factors — can be rooted in the consociational principle of making key decisions based, paradoxically, on the notorious political confessionalism. The peculiarities of the Lebanese political model (although they are subject to well-deserved criticism) distinguish it from the multitude of “customary” democracies, bringing together with examples of the unique democratic systems of Europe and other continents. The motley confessional composition of society, along with the historically determined foreign policy guidelines of individual communities, suggested a special informal decision-making mechanism throughout the country — not on the basis of majority power, but on a contractual, compromise principle. Leading theorists of consociationalism often had in mind the Lebanese pattern of democracy in their political studies, and many of their developments are still well applicable for analyzing the functioning of the main state institutions of Lebanon. A theoretical study, along with an analysis of the current regional situation, convince the author of the correctness of the hypothesis put forward. Both in Lebanese history and now, it is the inveterate forms of external influences that forced Lebanese society to balance on the verge of aggravated intercommunal clashes. The combination of external factors served as the beginning and further warmed up the civil war. Heightened relations with Syria by 2005, the Israeli attack in 2006, the gravest threat from jihadi-caliphatists – all these factors have negatively affected intra-civil and inter-group relations. Stereotypical forms of use of religious communities (Shiites, Sunnis, Christians of different denominations, etc.) from the outside and even direct pressure from abroad continue to confront them, imposing ideas on social relations and political participation that are alien to Lebanese. Diversification of political and business contacts of Russia with representatives of different Lebanese communities can serve as a good example of Lebanon’s perception of all the features of its political system as a full subject of international relations.